2008
DOI: 10.1002/ca.20685
|View full text |Cite
|
Sign up to set email alerts
|

The gracilis muscle and its use in clinical reconstruction: An anatomical, embryological, and radiological study

Abstract: The gracilis muscle is used widely in reconstructive surgery, as a pedicled or as a free microsurgical flap, for soft tissue coverage or as a functioning muscle transfer. Many studies, based on cadaver dissections, have focused on the vascular anatomy of the gracilis muscle and provided different data about the number, origin, and caliber of its vascular pedicles. Computed tomographic (CT) angiography of both thighs of 40 patients (35 males and 5 females, mean age: 63 years) have been analyzed to provide a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 32 publications
(43 reference statements)
0
31
0
3
Order By: Relevance
“…Surgery necessarily alters the vascular architecture of tissues, and it has been shown that local vascular morphology is universally altered, with the source vessels supplying cutaneous tissues often markedly different to that expected. In addition, maintenance of the caliber of vessels within the flap was highlighted in the current study, with the absence of sympathetic tone after flap transfer an established phenomenon [5,14]. This is one of the many anatomic and physiologic changes that occur following flap transfer or any surgical intervention.…”
Section: Discussionmentioning
confidence: 59%
“…Surgery necessarily alters the vascular architecture of tissues, and it has been shown that local vascular morphology is universally altered, with the source vessels supplying cutaneous tissues often markedly different to that expected. In addition, maintenance of the caliber of vessels within the flap was highlighted in the current study, with the absence of sympathetic tone after flap transfer an established phenomenon [5,14]. This is one of the many anatomic and physiologic changes that occur following flap transfer or any surgical intervention.…”
Section: Discussionmentioning
confidence: 59%
“…Length of muscle in both male &femal was more compared to others studies, muscle belly in male is more when compared to theirs studies &less in females compared tohurbanetal [9], total tendon length in both male & femal is more compared to others study, distal tendon length in both male & femal is more compared to others study, pedicle length from origin was less compared to vigatoetal [5], morrisetal [10], machii vetal [13], rajeshwarietal [14], lainetal [2] studies and more compared to Hurban etal 9 , Hussy et al [11], Dorothee etal [15]. Gracilis muscle derives its vascular supply from a wide range of arteries.…”
Section: Discussionmentioning
confidence: 71%
“…Within surgical departments, the need for professionals in human gross anatomy is uncontested (Fasel et al, 2005). In our experience, anatomic and clinical research examines anatomical structures from new perspectives (Macchi et al, 2007b(Macchi et al, ,c, 2008 and can lead to improved surgical practice (Tiengo et al, 2004(Tiengo et al, , 2007Macchi et al, 2005). In our project, the continuity of the diagnostic and therapeutic phases was achieved by the active involvement of residents in the steps involved in donation of body parts.…”
Section: Discussionmentioning
confidence: 96%